1994
DOI: 10.1007/bf02168086
|View full text |Cite
|
Sign up to set email alerts
|

Teacher-ratings and self-ratings of social competency in adolescents with low- and high-depressive symptoms

Abstract: A comparison of teacher-ratings and self-ratings of adolescents' social competency was investigated. One hundred five high school students completed the Reynolds Adolescent Depression Scale (RADS; Reynolds, 1987) and were divided according to their scores into three groups: the lowest quartile [low-depressive symptoms (LDS) group (n = 27)], the highest quartile [high-depressive symptoms (HDS) group (n = 28)], and the remainder. Students also rated themselves and were rated by their teachers on a social compete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Findings in the current study support the hypothesis that social skills would be significantly negatively correlated with internalizing symptoms. This finding is congruent with the previous research that has identified a concurrent negative relationship between social skills and internalizing symptoms (Blechman et al, ; Cole et al, ; Dalley et al, ; Kennedy et al, ; Wierzbicki & McCabe, ). This would be consistent with the view that social skill deficits have either a causal influence (Cole, ; Cole et al, ; Lewinsohn, ) or act as a vulnerability factor in (Segrin & Flora, ) the development of internalizing symptoms in children.…”
Section: Discussionsupporting
confidence: 91%
“…Findings in the current study support the hypothesis that social skills would be significantly negatively correlated with internalizing symptoms. This finding is congruent with the previous research that has identified a concurrent negative relationship between social skills and internalizing symptoms (Blechman et al, ; Cole et al, ; Dalley et al, ; Kennedy et al, ; Wierzbicki & McCabe, ). This would be consistent with the view that social skill deficits have either a causal influence (Cole, ; Cole et al, ; Lewinsohn, ) or act as a vulnerability factor in (Segrin & Flora, ) the development of internalizing symptoms in children.…”
Section: Discussionsupporting
confidence: 91%
“…Although the direct association between depressive symptoms and self-perceived social competence in children with HFASD has yet to be examined, studies of this kind conducted in non-ASD populations have revealed negative associations between depression and self-perceived social competence in both normal adults (Cole, Lazarick, & Howard, 1987;Connolly, 1989;Lewinsohn, Mischel, Chaplin, & Barton, 1980;Vanger, 1987;Youngren & Lewinsohn, 1980), children (Blechman et al, 1986;Dalley, Bolocofsky, & Karlin, 1994;Jacobsen, Lahey, & Strauss, 1983;Spirito, Hart, Overholser, & Halverson, 1990;Wierzbicki & McCabe, 1988) and students with learning disabilities (Haager & Vaughn, 1995). Depression, Self-perception, and Intellectual Ability Some studies on HFASD populations have added valuable insight to the link between intellectual ability and depression.…”
Section: Self-perceived Social Competence and Depression In Hfasdmentioning
confidence: 97%
“…Based on the research with normal (Chan, 1997;Dalley et al, 1994;Hymel, Rubin, Rowden, & LeMare, 1990;Jacobsen et al, 1983), learning disabled (Haager & Vaughn, 1995), and intellectually disabled populations (Benson & Ivins, 1992;Reiss & Rojahn, 1993) where associations between self-perceived competence and depressive symptoms have been found, it was predicted that children with HFASD, who perceived themselves as less socially competent, would report higher levels of depressive symptomatology. This hypothesis was supported.…”
Section: Self-perceived Social Competence and Depressive Symptomatologymentioning
confidence: 99%
“…Gabriel et al (2009) described social competencies as the ability "to continually develop and share ideas, promote their own position against contrary opinions and compromise despite linguistic and cultural barriers" (p. 1251). Even though researchers have used different terms to refer to social competencies, in many studies researchers have concluded that positive relationships between social competencies and academic achievement do exist (Anderson & Messick, 1974;Chen et al, 2010;Dalley, Bolocofsky, & Karlin, 1994;Tan et al, 2010).…”
Section: Social Competenciesmentioning
confidence: 99%